(untitled) (Research, Society and Development, 2022)
Objective. The aim of the study is to analyze the microbiota of the maxillary sinus of sheep as a viable biome to carry out experimental studies of biomaterials. Materials-Methods. 13 sheep (eight in isolation and five loose created) were used, making 26 maxillary sinuses, where swabs were performed by an extra-oral approach for microbiological analysis. Statistical tests such as Fisher’s exact test, Mann Whitney U test, chi-square test, and proportional means were used in the experiment. Results. Only eight maxillary sinuses had positive bacterial growth. The presence of Staphylococcus aureus was statistically significant relative to other microorganisms found. On the other hand, among the animals in isolation and those raised loose, there was no statistically significant difference in the presence of Staphylococcus aureus. Conclusion. Staphylococcus aureus is the predominant bacteria in the maxillary sinus of this experimental model. The difference in environment and feeding did not influence the microbiota of the maxillary sinus.